Pre-service EFL teachers’ language assessment literacy satisfaction and assessment preparedness - Farmasari, Santi; Wardana, Lalu Ali; Baharudin, Baharudin; Herayana, Desi; Suryaningsih, Hartati (International Journal of Language Education, 2023)
Pre-service teachers' ability to construct and conduct assessment has been a point of emphasis for decades, and rightfully so. It is crucial that they acquire the necessary knowledge and abilities in their language assessment course during their pre-service teacher education to effectively assess students in their future professional routines. The purpose of this research was to determine if and how pre-service English teachers' (PSETs) satisfaction with their language assessment course corresponded with their level of readiness. 51 out of 56 PSETs participated since they met the two requirements (passing the language assessment course and enrolling in TAP). The Fulcher (2012) language assessment literacy questionnaire was adapted and disseminated. The questions were organized into four categories for the purpose of analysis: overarching principles and concepts in linguistic assessment; designing language assessment; scoring test items and analyzing test results. Results demonstrated that LAL satisfaction was not congruent with assessment readiness. There was a "neutral" level of satisfaction among participants (51.5 percent), but they were nearly set to begin practicing assessment at their TAP (78.5 percent). Additionally included are statistics that are specific to each of the four categories found in the questionnaire.  In particular, the study suggests that training in evaluating open-response questions and analyzing test items warrants expansion. Additional research could fill in the gap between LAL satisfaction and the PSETs by examining the relationship between the two.